2006
DOI: 10.1590/s1519-69842006000400002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic cycle and dynamics of aquatic macrophytes in two intermittent rivers of the semi-arid region of Brazil

Abstract: The dynamics of aquatic macrophytes in intermittent rivers is generally related to the characteristics of the resistance and resilience of plants to hydrologic disturbances of flood and drought. In the semi-arid region of Brazil, intermittent rivers and streams are affected by disturbances with variable intensity, frequency, and duration throughout their hydrologic cycles. The aim of the present study is to determine the occurrence and variation of biomass of aquatic macrophyte species in two intermittent rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
0
16
1
1
Order By: Relevance
“…Other researchers, however, have reported lower diversity levels than those encountered in the present study: Reis & Barbosa (1993) encountered only 14 aquatic macrophytes species in Mares Lake in the municipality of Lagoa Santa (MG); Bini et al (2005) identifi ed 16 taxa in the Cachoeira Dourada reservoir (GO/MG); while Pedro et al (2006) reported the occurrence of only nine species while examining the dynamics of macrophyte occupation of reservoirs in the semiarid region of Bahia State.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Other researchers, however, have reported lower diversity levels than those encountered in the present study: Reis & Barbosa (1993) encountered only 14 aquatic macrophytes species in Mares Lake in the municipality of Lagoa Santa (MG); Bini et al (2005) identifi ed 16 taxa in the Cachoeira Dourada reservoir (GO/MG); while Pedro et al (2006) reported the occurrence of only nine species while examining the dynamics of macrophyte occupation of reservoirs in the semiarid region of Bahia State.…”
Section: Discussioncontrasting
confidence: 67%
“…Research efforts already undertaken in northeastern Brazil include: Barbieri & Pinto (1999) in Maranhão State; Matias & Nunes (2001) and Matias et al (2003) in Ceará State; França et al (2003) in Bahia State; and Pedro et al (2006) in Paraíba State.…”
Section: Introductionmentioning
confidence: 99%
“…Pedro et al (2006) analyzed the hydrological cycle and the dynamics of macrophytes in intermittent rivers of the semi-arid region of Paraíba (northeastern Brazil) and found that the occurrence of seasonality (dry and rainy season) is a determining factor that is related to the strength and resilience of these plants. Comparing the number of species in urban and non-urban areas of the Cuyahoga River (Ohio, USA), Balanson et al (2005) observed that there was no apparent correlation between the nutrient content of the streams and the degree of impact on macrophyte communities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on aquatic ecosystems of the Brazilian semi-arid region have evidenced the high biodiversity of these environments, including aquatic macrophytes, and have demonstrated that patterns of diversity are related to the hydrological extremes of flood and drought (Medeiros and Maltchik, 1999;Silva-Filho and Maltchik, 2000;Medeiros and Maltchik, 2001;Pedro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%